TINJAUAN SUNGAI ITEM SUNTER SETELAH DINORMALISASIKAN SEBAGAI PENGENDALIAN BANJIR DI JAKARTA PUSAT - Fadhel Amri Aji; Arris Maulana; Rosmawita Saleh (Menara: Jurnal Teknik Sipil, 2021)
The purpose of this research to review the Item Sunter River which has been normalized as flood control in Central Jakarta. This research was conducted to determine the causes of flooding due to the overflow of the river that occurred in 2020. The review was carried out by analyzing the flood discharge of the river by calculation of the planned flood discharge using the Nakayasu Synthesis Unit Hydrograph method in return periods of 2, 5, 10, 25, and 50 years respectively of 88.44 m3/s, 116.52 m3/s, 137.85 m3/s, 168.39 m3/s, and 193.22 m3/s compared to the calculation river flow rate using the Manning equation of 205.94 m3/s. The calculation result shows that river flow is still sufficient for the planned flood discharge. Then a further analysis is carried out on the factors of waste management, sedimentation, and pump house. The results of the analysis show that the accumulation of garbage occurs in the river basin area, sedimentation is 20% of the flow capacity, and the pump house is inadequate due to flooding. Therefore, it is necessary to prevent and clean up rubbish in river area, routine dredging sedimentation, and maintenance of water pumps must be on standby at all times.